Audit quality and audit report lag: Case of Indonesian listed companies - Rusmin, Rusmin; Evans, John (Emerald Group Publishing Limited, 2017)
Purpose: The purpose of this paper is to empirically examine the relation between two dimensions of auditor quality, namely, auditor industry specialization and auditor reputation and the audit report lag. Design/methodology/approach: The data collection focuses on companies listed on the Indonesia Stock Exchange for the financial year of 2010 and 2011. To ensure data homogeneity and reduce industry bias, this study focuses solely on manufacturing companies identified by the Indonesian Capital Market Directory. Findings: This study finds a negative and significant association between industry-specialist auditors and audit report timeliness. Companies audited by industry-specialist auditors have shorter audit delays. The authors also find evidence that Big 4 auditors perform significantly faster audit work than their non-Big 4 counterparts. In addition, this study reports a statistical and significant relationship between auditing complexity, companies' profitability, auditors' business risk, and industry classification and audit report lag. The results show that firms with a large number of subsidiaries and firms experiencing poorer financial performance are found to be associated with longer reporting delays. Moreover, audit report timeliness is found to be faster for companies in the low-profile industry sector and owned by family members. Research limitations/implications: Similar to other empirical investigations, this study is not without certain caveats. First, the period of audit report lag in this study reflects the audit work from the year-end to the audit report date. The authors do not consider audit work conducted outside this period in the analysis. Second, there are numerous control variables and although the authors have attempted to capture those variables to maintain the integrity of the research there are likely other excluded variables that may be important in explaining audit report timeliness. Finally, there are other factors, for example, an administrative approval process with the audit firm home office, which can affect audit report lags but have not been included in the model analysis. Future studies can seek to focus on refinements to the proxy measures for dependent and experimental variables. Practical implications: Insights drawn from this study may be of assistance to policy makers as they consider the costs and benefits associated with varying levels of audit market concentration as well as providing a snapshot of the level of non-compliance on audit timeliness in Indonesia. Originality/value: This study provides further empirical evidence on the relation between auditor quality and audit report lag using data from a different domestic setting. This study also enriches the auditor quality literature by employing industry-specialist and Big 4 auditors as a predictor for the timeliness of audit reports.